International Legal Aspects of Regulating the Use of Transboundary Rivers in Central Asia - ZHUNUSBEKOVA, Aigerim Zhunusbekovna; ABASHIDZE, Aslan Khuseinovich; TLEPINA, Sholpan Valerievna (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
Water resources in Central Asia have always had and continue to have a significant impact on economic activities of the states of the region since all the major rivers here are transboundary and there are disagreements between the countries of the region about water supply and sharing of water resources. There are also disagreements on the application of norms of international law in the sphere of international legal regulation of transboundary water resources. The purpose of this article is to study international legal problems of transboundary water resources use by Central Asia states. In the course of the work performed, general methodological principles are used: system approach when analyzing the conceptual apparatus of the topic; comparative legal method when analyzing international treaties, acts, laws on the use of transboundary waters; method of historical analysis when studying the formation and development of international cooperation of Central Asian states in the field of transboundary water resources use.In this article, based on the study of international legal norms, the practice of their application in the field of cooperation of states on use of transboundary water resources, the problems and prospects for development of international legal regulation of cooperation of states in use and management of transboundary water resources in Central Asian region are identified.